EVALUASI KEBIJAKAN PROGRAM SRIKANDI DI LEMBAGA SENSOR FILM KEMENTERIAN KEBUDAYAAN REPUBLIK INDONESIA - Eka Pratama, M. Rifa'i; Saprudin; Iskandar, Abubakar (Administratie: Jurnal Administrasi Publik, 2025)
Technological advancements impact various aspects of life, including the governance aspect. The Indonesian government developed an application program aimed at improving the efficiency and effectiveness of correspondence and archiving, which was then named the Integrated Dynamic Archival Information System (Srikandi). This research was conducted to evaluate the implementation of the Srikandi program at the Film Censorship Institute of the Ministry of Culture of the Republic of Indonesia, in order to determine the level of success of the Srikandi implementation at the LSF of the Ministry of Culture of the Republic of Indonesia, as well as to analyze the obstacles faced and the efforts made by policy implementers to overcome these obstacles. The method used is a descriptive qualitative method with implementation theory from Merilee S. Grindle, which analyzes from the content and context aspects, and evaluates the implementation with the theory from Bridgman & Davis with four dimensions: input, process, output, and outcome. The success of the implementation of the Srikandi program policy at the LSF of the Indonesian Ministry of Culture is considered to have been quite good, as seen from the research results through in-depth interviews with informants, supporting documents, and the outcomes of the Srikandi program implementation.